2017
DOI: 10.7860/jcdr/2017/25604.9989
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Female Patients with Subclinical Hypothyroidism by Brainstem Auditory Evoked Potentials: Case-Control Study

Abstract: Introduction: Hypothyroidism, a common endocrinological disorder is quite prevalent in its subclinical state in the adult population. Nervous system involvement is frequent in hypothyroidism with documentation of peripheral and central conduction delays as abnormal latency prolongations in Brainstem Auditory Evoked Potential (BAEP) records. Subclinical hypothyroidism however, has been less extensively studied for investigating the involvement of the auditory functions. Aim:To assess the auditory functions and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 17 publications
0
1
0
Order By: Relevance
“…Subclinical hypothyroidism leads to overt hypothyroidism. [ 10 ] The most important cause of hypothyroidism is autoimmunity. [ 12 ] Elevated levels of antibodies against thyroid peroxidase and thyroglobulin were reported in 60% subclinical hypothyroid subjects.…”
Section: Discussionmentioning
confidence: 99%
“…Subclinical hypothyroidism leads to overt hypothyroidism. [ 10 ] The most important cause of hypothyroidism is autoimmunity. [ 12 ] Elevated levels of antibodies against thyroid peroxidase and thyroglobulin were reported in 60% subclinical hypothyroid subjects.…”
Section: Discussionmentioning
confidence: 99%
“…These data are scarcer and more conflicting for subclinical hypothyroidism (SCH). Recently, it was shown that adult women with SCH had increased absolute latency of waves I, III, and V in ABR and increased interpeak latency of intervals III-V and I-V bilaterally, when compared to age-and sex-matched controls [30]. Paladugu et al (2015) also showed an impairment of the cognitive function in individuals aged 12 to 45 years by analyzing evoked auditory potentials (P300), with increased latency in patients with SCH.…”
Section: Plos Onementioning
confidence: 99%